The effect of total intravenous versus inhalation anesthesia on early postoperative pain after laparoscopic cholecystectomy: A randomized controlled trial from Eastern Libya: Propofol versus isoflurane for early postoperative pain - Alhussadi, Hamza M.; Noisari, Saja S.; Alhassi, Esraa M.; Makhlouf, Salim M. (Journal of Surgery and Medicine, 2026)
Background/Aim: Effective postoperative pain (POP) control remains a major determinant of recovery after laparoscopic cholecystectomy (LC), particularly in resource-limited healthcare settings such as Libya. Although propofol-based total intravenous anesthesia (TIVA) may improve early analgesia compared with isoflurane-based inhalation anesthesia (IA), comparative evidence from these settings is limited. This trial compared acute POP trajectories during the first 24 hours after LC under these two anesthetic techniques in Eastern Libya. Methods: This prospective, double-blind, randomized controlled trial was conducted at two public hospitals in Eastern Libya between February and May 2025. Fifty-nine patients scheduled for elective LC were analyzed after randomization to propofol-based TIVA (n = 29) or isoflurane-based IA (n = 30). The primary outcome was pain intensity measured with the Numerical Rating Scale (NRS; 0-10) at 2, 6, 12, and 24 hours postoperatively. Data were analyzed using SPSS version 26. Results: A significant anesthesia-by-time interaction was observed for postoperative pain scores (F[2.92, 166.63] = 11.67, P < 0.001). Pairwise comparisons showed lower mean pain scores in the TIVA group at 2 hours [4.3 (0.8) vs. 4.8 (0.8), P = 0.010] and 12 hours [2.2 (0.5) vs. 2.7 (0.6), P = 0.001]. The 6-hour difference was smaller [3.2 (0.6) vs. 3.4 (0.7), P = 0.028], and no significant difference was observed at 24 hours [1.5 (0.3) vs. 1.7 (0.4), P = 0.063]. The main effect of anesthetic type was not significant (F[1, 57] = 2.21, P = 0.143). Conclusion: Propofol-based TIVA was associated with modestly lower early postoperative pain scores after LC compared with isoflurane-based IA, but this benefit was not sustained at 24 hours. Selection of anesthetic technique should consider whether early POP control is a clinical priority within the broader multimodal analgesia strategy.